PENERAPAN MESIN PEMUTAR UNTUK MENINGKATKAN PRODUKTIVITAS DAN KUALITAS ES PUTER - Suwahyo, Suwahyo; Khumaedi, Muhammad (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2016)
This activity was carried out with the aim to resolve the problems faced by the partner with businesses in the field of making traditional ice cream in Semarang. The implementation employed the following methods; with lecture / extension for the theoretical material and motivation, demonstration to deliver practical material / skills, direct practice by partners, and mentoring activities. The results of community service activities are: 1) in the aspect of production, a set of machine ice cream maker was produced, two sets of coconut grater machines, supporting equipment of ice cream production, and the arrangement of the production site, 2) In the aspect business management, the partners have been given assistance on simple accounting, promotions, and marketing of products, 3) the partner may improve the productivity and quality of products that have an impact on increasing revenues.